Prognostic significance of argyrophilic nucleolar organizer region (AgNOR) counts and nutritional status in pediatric acute lymphoblastic leukemia (ALL). - Wisman Herminto Wisman Herminto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Background: The cell proliferation rate is a well-established prognostic factor in cancer, but it has not been considered as a prognostic factor used to stratify ALL patients into risk groups.Objective: The main goal of this study was to verify the relationship between AgNOR number and nutritional status, at the time of diagnosis, and remission induction response rate and survival in ALL patients. Methods: Smears of marrow aspirates from 35 newly diagnosed and previously untreated ALL patients were stained, at presentation, by silver method and evaluated by counting the mean AgNOR number of each case. Anthropometric nutritional status was obtained also for each patient.Results: The mean AgNOR number of the whole series was 3.54 Â± 0.74. It was significantly higher in resistant patients than in patients who achieved complete remission (p = 0.01). It was found that the mean AgNOR number = 4 was related to the lower remission induction response than the mean AgNOR number < 4 (p = 0.02). Multivariate analysis by Cox regression model showed that the mean AgNOR number retained its prognostic significance as a predictor of survival (p = 0.04). Conversely, nutritional status was not correlated with remission induction response, and was not of prognostic significance, either.Conclusion: AgNOR number at diagnosis is a reliable prognostic parameter to predict remission induction response rate and survival in childhood ALL, and should be rountinely introduced in the group risk definition.Keywords: AgNOR - nutritional status - prognostic factor - pediatric ALL